Encyclopedia of the Anthropocene - DellaSala, Dominick A., 1956-; Goldstein, Michael I. (Elsevier, 2018)
"Encyclopedia of the Anthropocene presents a currency-based, global synthesis cataloguing the impact of humanity's global ecological footprint. Covering a multitude of aspects related to Climate Change, Biodiversity, Contaminants, Geological, Energy and Ethics, leading scientists provide foundational essays that enable researchers to define and scrutinize information, ideas, relationships, meanings and ideas within the Anthropocene concept."